Atividade de enzimas que degradam nucleotídeos e nucleosídeo de adenina em plaquetas de pacientes com tireoidite de Hashimoto em tratamento com levotiroxina sódica - Noal, Cristiano Bicca (2012)
Hashimoto Thyroiditis (HT) or chronic lymphocytic thyroiditis is an autoimmune disease that causes the destruction of the thyroid gland by inflammatory infiltrates and consequently loss of function. This disease is spread worldwide and predominantly affects females. The consequences of alterations in its activity range from cretinism to the vascular changes. It is known that the enzymes ectonucleoside diphosphohydrolase triphosphate (E-NTPDase, EC 3.6.1.5, CD39), ecto-5'nucleotidase (EC 3.1.3.5, CD73) and adenosine deaminase (ADA, EC 3.5.4.4) are involved in regulating the immune response and thrombotic events, since they regulate extracellular levels of adenine nucleotides and nucleoside. Since HT patients have an autoimmune response and present microvascular changes, the objective of this study was to evaluate the influence of purinergic signaling in the regulation of microvascular dysfunction triggered by the disease determining the activity of the ectoenzymes involved in the metabolism of ATP in platelets from patients with HT in treatment with levothyroxine. Samples were collected from patients with HT treated with levothyroxine and from a control group. In this study we determined the activity of the enzymes E-NTPDase, ecto-5'-nucleotidase and E-ADA; detected the expression of the enzyme in platelets and E-NTPDase; and measured hormone levels of TSH and fT4 in patients with HT treated with levothyroxine and control group. Results obtained in the enzyme activity showed that patients with HT in hormone replacement with levothyroxine presented no significant changes when compared with the control group. In conclusion, levothyroxine used in patients with HT may reverse the effects of hypothyroidism when used regularly in these patients, while maintaining the enzyme activity in basal levels.